Analisis Kegiatan Kuliah Kerja Nyata Kelompok 38 STAIN Madina Di Desa Hajoran - Siti Olom Harahap; Muhammad Fatwa Arrozi; Siti Hannida Harahap; Hanapi Rangkuti; Lailan Nur Rangkuti; Muhammad Arif Daulay; Lailan Saadah Mardia; Novia Eriza; Maharani Harahap (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
This activity aims to complete the assignment of a real work study report (KKN) regarding community service." The realization is in the form of mutual cooperation in maintaining the cleanliness of neighborhood roads, cemeteries, mosques and public areas. Going directly into the field to carry out reciprocal collaboration with local communities is the research method applied. The following are the results of the activities carried out: picking up and sorting rubbish, cleaning grass, cleaning the surrounding environment, cleaning the mosque and surrounding roads, helping others, and helping local women in the kitchen. Students' contributions to society in carrying out social interests is one of the advantages of research. The photos and mutual cooperation efforts to provide assistance to the Hajoran village community are the results of this investigation.